Design, analysis, and fabrication of mini size spring roll maker / Afiq Rahman Mohammad - Afiq Rahman, Mohammad (2022)
The spring roll also known as “Popia” is a regarded as one of the most famous snack choice in Malaysia. It is easy to make and it’s ingredients are also cheap. Although it is easy to make, the spring roll production at a larger scale can be burdensome to other especially to stall traders that sells spring roll or families who wishes to make a large batch of spring rolls. The process of making spring rolls in larger batches can be time consuming and uses loads of energy. This project aims to design, analysis, and fabricate a Spring Roll Maker that can make spring roll as many as possible to suit the needs of the user. Three designs will be drawn and analysed to determine the effectiveness of the product and to determine the best material to be used. Then, the final design sketch will be developed into parts and assembled into a complete product using SolidWorks software. The parts will also be analysed using the SolidWorks software. After the suitable materials has been picked, the product will be fabricated using various tools that is suitable for the fabrication process